Anderemaeus (Acari, Oribatida)—overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny - Norton, Roy A.; Ermilov, Sergey G. (Zootaxa, 2019)
Anderemaeus is a genus of Gondwanan soil-dwelling oribatid mites with seven of the eight previously known species being South American. We propose two new species from Chile— A. sidorchukae sp. nov. and A. dentatus sp. nov.—and a third from Ecuador, A. mataderoensis sp. nov. Juveniles of the former two species are described, comprising the first such data for Anderemaeidae: nymphs notably lack both exuvial scalps and centrodorsal gastronotic setae, and the opisthonotal gland opens on a distinct stalk. The generic description is revised and expanded and a key to known species of Anderemaeus is presented, including A. tridactylus comb. nov. We reject the inclusion of Anderemaeus in a broad concept of Caleremaeidae and the implied subsumption of Anderemaeidae, as there are no synapomorphies linking the taxa. Anderemaeus species possess derived traits—e.g. adult with circumpedal carina and nymphs with smooth cuticle and no scalp retention—that are absent from Caleremaeus but are shared with more derived brachypyline taxa. The higher classification of Anderemaeus is reviewed: an analysis of known traits is inconclusive regarding both the generic composition of Anderemaeidae and its superfamilial relationships. However, on the strength of juvenile morphology, we propose the transfer of Anderemaeidae to Gustavioidea.